Nε-(carboxymethyl)lysine and Nε-(carboxyethyl)lysine in tea and the factors affecting their formation. (1st October 2017) - Jiao, Ye; He, Jialiang; Li, Fengli; Tao, Guanjun; Zhang, Shuang; Zhang, Shikang; Qin, Fang; Zeng, Maomao; Chen, Jie
Highlights: The CML and CEL contents of 99 different tea samples were determined by LC–MS/MS. The CML and CEL levels in the teas were high and could not be ignored. Dark and black tea showed higher levels of CML and CEL than green and oolong tea. There were significantly negative correlations between catechins and CML/CEL. Abstract: The levels of N ε -(carboxymethyl)lysine (CML) and N ε -(carboxyethyl)lysine (CEL) in 99 tea samples from 14 geographic regions, including 44 green, 7 oolong, 41 black, and 7 dark teas were determined by liquid chromatography-tandem mass spectrometry (LC–MS/MS). The CML and CEL contents varied from 11.0 to 1701 μg/g tea and 4.6 to 133 μg/g tea, respectively. Dark tea presented the highest levels of CML and CEL, whereas green and oolong teas presented the lowest levels. Five kinds of catechins in the tea were also analyzed, and spearman's correlation coefficients showed that all the catechins negatively correlated with CML and CEL. The results suggested that withering, fermentation and pile fermentation may facilitate the formation of CML and CEL. Catechins might inhibit the formation of CML and CEL, but their inhibitory effects may be affected by tea processing. The results of this study are useful for the production of healthier tea.